Answer:
Explanation:
13) -10x = x -33
-10x - x = -33
-11x = -33
x = -33/-11
x =3
14)-10x - 11 = x - 33
-10x -x = -33 + 11
-11x = -22
x = -22/-11
x = 2
15) 4x + 4 = -3x - 17
4x + 3x = -17 -4
7x = - 21
x = -21/7
x = (-3)
16) 2x - 7 = 4x +12
2x - 4x = 12 + 7
-2x = 19
x = 19/-2
x = -19/2
17) 2x +7 = 4x +12
2x - 4x = 12 - 7
-2x = 5
x = 5/-2
x = -5/2
18) -2x +7 = -4x +12
-2x + 4x = 12 -7
2x = 5
x = 5/2
19) x + 5 = -3x -10
x + 3x = -10 - 5
4x = -15
x = -15/4
20) 15x +10 = 10x +10
15x - 10x = 10 - 10
5x = 0
x = 0
21) = -x + 3
-x = 2*(-x + 3)
-x = -2x + 6
-x + 2x = 6
x = 6
22) = x - 3
3x = 4 * ( x - 3)
3x = 4*x - 4*3
3x = 4x - 12
3x - 4x = -12
-x = -12
x = -12/-1
x = 12
23)
24)
5.7m questions
7.4m answers